Computers, schools and students : the effects of technology - Cullingford, Cedric (Monitoring change in education., 2009)
Using research from a variety of secondary schools, the authors suggest ways to enable reality to match the ambitious expectations of political initiatives and investment in ICT in schools. This informative book is of importance, not only to teachers but also to educational researchers and policy-makers.